Daylighting Strategy for Enclosed Spaces Office in UTHM Pagoh - Shaiful Nizam, Ainul Mardhiah; Omar Shukir@Shukri, Nur Hasya Husna; Aslila Abd Kadir, (Multidisciplinary Applied Research and Innovation, 2024)
Daylight is the light that is transmitted by sunlight and reflected on a surface to illuminate a space or area. Generally, windows can give appropriate illumination up to 1.5 to 2 times the vertical height of the floor. At UTHM Campus Pagoh, there are some rooms in block A1 that do not get natural light and are completely dependent on electricity. So, the light pipe system is one of the statergy that can be used to reduce the use of electricity. This is because the light pipe system is a linear device that can bring natural light into the interior by capturing, transmitting and reflecting it. According to the Malaysian Standard (MS) 1525:2014, working spaces like offices and classrooms should have lighting levels between 300 and 500 lux. After identifying the enclosed space through the plan found, the lux and temperature readings in the room are taken for comparison. The simulation was made in DIALux and found that the average illuminance of the room exceeded the MS 1525:2014 lighting level. Light pipe system simulation is made in holigilm and found that light reduction can be done. By using the light pipe system, this can reduce electricity and sunlight can benefit health. These potential reductions would be extremely beneficial in encouraging sustainable solutions in daylighting strategies using a light pipe system, particularly under Malaysian sky conditions.